Answer:
= x(a+b)(a-b) . x(b+c)(b-c) .x(c+a)(c-a)
You plug -x+16 in for y in x+4y=37 to get x after you multiply x+4y=37 by -1.
-x-4(-x+16)=-37
-x+4x-64=-37
3x-64=-37
3x=27
x=9
Then you plug 9 into either equation to get y.
y=-x+16
y=-(9)+16
y=7
x=9 and y=7
translate each statement into mathematical language
length is nine inches less than twice width. L = 2W - 9
perimeter is 84 inches 2L +2W = 84
Substitute the expression for L (2W-9) for L in the second equation resulting in the follwing
2(2W-9) + 2W = 84
4W - 18 + 2W = 84
(4W+2W) = 84+18
6W = 102
W = 102/6 = 51/3
L = 2(51/3) - 9
= L= 17-9
L=6
Answer:
z=4/3
z=-1/3
Step-by-step explanation:
|6z-3|=5
1. 6z-3=5 6z=8 z=4/3
2. 6z-3=-5 6z=-2 z=-1/3